Recognition and the resurrection appearances of Luke 24 - Thompson, Alexander; Walter de Gruyter GmbH & Co. KG (Berlin/Boston Walter De Gruyter GmbH, 2023)
The series Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft (BZNW) is one of the oldest and most highly regarded international scholarly book series in the field of New Testament studies. Since 1923 it has been a forum for seminal works focusing on Early Christianity and related fields. The series is grounded in a historical-critical approach and also explores new methodological approaches that advance our understanding of the New Testament and its world.
Intro -- Acknowledgements -- Contents -- Chapter 1 Introduction -- Chapter 2 History of Scholarship and Methodology -- Chapter 3 Recognition in Greek and Roman Literature -- Chapter 4 Recognition in the Hebrew Bible and Hellenistic Jewish Literature -- Chapter 5 Recognition in the Resurrection Appearances of Luke 24 -- Chapter 6 Recognition in Luke 24 And The Wider Narrative of Luke-Acts -- Chapter 7 Conclusion -- Bibliography -- Index.
"How are the resurrection appearances of Luke's Gospel shaped to offer a climax to the narrative? How does this narrative conclusion compare to the wider ancient literary milieu? Recognition and the Resurrection Appearances of Luke 24 proposes that the ancient literary technique of recognition offers a compelling lens through which to understand the climatic role of the resurrection appearances of Jesus as depicted in Luke 24. After presenting the development of recognition in ancient Jewish and Greco-Roman literature, Thompson demonstrates how Luke 24 deploys the recognition tradition to shape the form and function of the resurrection appearances. The ancient recognition tradition not only casts light on various literary and theological features of the chapter but also shapes the way the appearances function in the wider narrative. By utilizing recognition, Luke 24 generates cognitive, affective, commissive, and hermeneutical functions for the characters internal to the narrative and for the audience. The result is a compelling climax to Luke's Gospel that resonates with Luke's wider literary and theological themes. This work offers a compelling analysis of the Luke's Gospel in the ancient literary context in light of the ancient technique of recognition that will appeal to those interested in narrative approaches to the New Testament or the interpretation of the New Testament in the wider literary milieu."
Description based on publisher supplied metadata and other sources
Keywords: Jesus Christ -- Resurrection; Bible -- Criticism, Narrative; Bible.-New Testament; Bible.-Luke; Recognition in literature